Contested Knowledges: Water Conflicts on Large Dams and Mega-Hydraulic Development - Shah, Esha (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Water acquisition, storage, allocation and distribution are intensely contested in our society, whether, for instance, such issues pertain to a conflict between upstream and downstream farmers located on a small stream or to a large dam located on the border of two nations. Water conflicts are mostly studied as disputes around access to water resources or the formulation of water laws and governance rules. However, explicitly or not, water conflicts nearly always also involve disputes among different philosophical views. The contributions to this edited volume have looked at the politics of contested knowledge as manifested in the conceptualisation, design, development, implementation and governance of large dams and mega-hydraulic infrastructure projects in various parts of the world. The special issue has explored the following core questions: Which philosophies and claims on mega-hydraulic projects are encountered, and how are they shaped, validated, negotiated and contested in concrete contexts? Whose knowledge counts and whose knowledge is downplayed in water development conflict situations, and how have different epistemic communities and cultural-political identities shaped practices of design, planning and construction of dams and mega-hydraulic projects? The contributions have also scrutinised how these epistemic communities interactively shape norms, rules, beliefs and values about water problems and solutions, including notions of justice, citizenship and progress that are subsequently to become embedded in material artefacts.